2008
DOI: 10.1159/000126077
|View full text |Cite
|
Sign up to set email alerts
|

Isolates and Antibiotic Sensitivity of Eighty Culture-Proven Endophthalmitis Cases from Istanbul

Abstract: Purpose: To investigate the spectrum of organisms causing endophthalmitis and their sensitivity to commonly used antimicrobial agents. Methods: Medical records of 80 consecutive patients treated at Beyoglu Eye Hospital for endophthalmitis from January 2001 to April 2006 were reviewed. Specimens were obtained from either the vitreous (93%, 81/87) or anterior chamber (7%, 6/87) during pars plana vitrectomy or vitreous tap, and were inoculated into blood culture bottles. A Kirby-Bauer disk diffusion test was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
6

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 15 publications
1
6
0
6
Order By: Relevance
“…However, this may trigger antibiotic resistance. In two previous studies, it was shown that 68% of CoNS were sensitive to third generation quinolones (10)(11) . We showed a 92%-susceptibility to ciprofloxacin in our previous report (9) .…”
Section: Discussionmentioning
confidence: 95%
“…However, this may trigger antibiotic resistance. In two previous studies, it was shown that 68% of CoNS were sensitive to third generation quinolones (10)(11) . We showed a 92%-susceptibility to ciprofloxacin in our previous report (9) .…”
Section: Discussionmentioning
confidence: 95%
“…Çal›flmam›z-da ise kültür pozitiflik oran› %61,7 oran›nda idi. Kültürde üretebilme oranlar› düflük oldu¤u için bu enfeksiyonlar, ampirik olarak topikal genifl spektrumlu antibiyotikler ile tedavi edilmektedir (10) (14). Florokinolonlara karfl› bu yüksek orandaki direncin etken patojenlerin daha çok gram pozitif koklar olmas› ve ampirik tedavide s›kl›k-la kullan›larak direnç geliflimine neden olmalar›ndan kaynaklanabilece¤i düflünülebilir.…”
Section: Tart›flmaunclassified
“…Katarakt ameliyatı en sık yapılan göz içi cerrahisi olduğundan postoperatif endoftalminin de en sık nedenidir [1]. Ancak oküler cerrahi sonrası endoftalmi insidansı katarak için % 0,04-% 0,19 iken bu oran trabekülektomi-de % 0.15, keratoplastide % 0,2, sekonder göz içi lensi implantasyonunda % 0,3 ve vitroretinal cerrahi sonrası % 0,15 olarak bildirilmiştir [2][3][4]. Klinik olarak endoftalmi tanısı konulan hastalardan alınan vitreus örneği kültüründe üreme oranı % 69 bulunmuştur [4,5].…”
Section: Introductionunclassified
“…Ancak oküler cerrahi sonrası endoftalmi insidansı katarak için % 0,04-% 0,19 iken bu oran trabekülektomi-de % 0.15, keratoplastide % 0,2, sekonder göz içi lensi implantasyonunda % 0,3 ve vitroretinal cerrahi sonrası % 0,15 olarak bildirilmiştir [2][3][4]. Klinik olarak endoftalmi tanısı konulan hastalardan alınan vitreus örneği kültüründe üreme oranı % 69 bulunmuştur [4,5]. Kültür pozitif örneklerde % 70 gram pozitif, koagü-laz negatif stafilakok türleri (özellikle S. Epidermitis), geriye kalan % 15 diğer gram pozitif, % 6 gram negatifler ve % 9 karışık bakteriler belirlenmiştir [5][6][7][8][9].…”
Section: Introductionunclassified
See 1 more Smart Citation